Modified unilateral periureteral injection technique in the treatment of patients with high-grade vesicoureteral reflux: A study of primary findings - Seyed Alaeddin Asgari; Afshin Safaei-Asl; Mandana Mansour-Ghanaie; Seyed Mohammad Asgari; Asghar Faryabi; Mohammadreza Bazli; Faezeh Emami Sigaroudi; Seyed Ahmad Naseri Alavi (Asian Journal of Urology)
Objective: Although endoscopic treatment has been used by many pediatric urologists for the treatment of vesicoureteral reflux (VUR), it has no considerable success in high-grade VUR. We aimed to describe the primary outcomes of unilateral periureteral injection technique (PIT), as well as bilateral PIT in high-grade VUR. Methods: In this prospective study, we examined 92 ureters in 45 boys and 40 girls from February 2010 to May 2018. Bilateral PIT and unilateral PIT were applied in 67 and 25 refluxing units, respectively. In the unilateral PIT, the subureteral injection site was only at the 5- or 7-o'clock position. However, in the bilateral PIT, the subureteral injection sites were at 5- and 7-o'clock position. Pre- and post-operative reflux grades were evaluated by voiding cystourethrography 6 months after surgery. Results: Seven patients had bilateral reflux. Overall, 75 (81.5%) ureters showed Grade IV VUR, while 17 (18.5%) had primary Grade V VUR. The mean age of the subjects was 39.2 months. In unilateral PIT ureters, VUR was resolved in 23 (92.0%) refluxing units. It was downgraded to Grade III in one ureter (4.0%) and to Grade II in another ureter (4.0%). In addition, in bilateral PIT cases, VUR was resolved in 60 (89.6%) ureters; it downgraded to Grades II and III in 3 (4.5%) and 4 (6.0%) refluxing units, respectively. Conclusion: Unilateral PIT can be highly effective in the treatment of selected ureters of high-grade VUR. However, further studies are needed to confirm our results.